Analisis Kebutuhan Bahan Ajar Booklet Bangun Datar dan Sifat-sifatnya untuk Siswa Sekolah Dasar/Madrasah Ibtidaiyah - Rohmah, Siti Nur; Yuniawatika, Yuniawatika; Madyono, Suhel (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2020)
This study aims to present the results of a needs analysis teaching material booklet flat build and its characteristics in class III B MI Qomarul Hidayah Trenggalek students. This research is descriptive research. The data were obtained from interviews with class III B MI Qomarul Hidayah Trenggalek teachers, the results of the documentation, and the results of a needs analysis questionnaire filling by 15 students of class III B MI Qomarul Hidayah Trenggalek in 2019/2020 academic year. From the results of a needs analysis questionnaire, it was obtained that students in class III B MI Qomarul Hidayah Trenggalek 86,7% needed teaching materials that had practical size, 93,3% needed additional learning resources about flat build and its characteristics more complete material, 93,3% needed practice exercises to measure understanding of the material flat build and its characteristics, 93,3% needed teaching materials that could be used for independent learning, and 100% agreed if booklet flat build and its characteristics were developed. It can be concluded that students of class III B MI Qomarul Hidayah Trenggalek agreed if booklet flat build and its characteristics were developed. The booklet developed was adjusted to the results of interviews with class III B MI Qomarul Hidayah Trenggalek teachers, the results of the documentation, as well as the results of filling the needs analysis questionnaire of students class III B MI Qomarul Hidayah Trenggalek namely: having a practical size, more complete material, there were exercises, and can be used for independent learning